Results of a double-blind, randomized, comparative, cross-sectional study of the pharmacokinetics and pharmacodynamics of genetically engineered human insulin preparations - Alexander Mayorov; Olga Avdeeva; Ekaterina Koksharova; Tatyana Belikova; Ekaterina Mishina; Roman Dray (Фармакокинетика и Фармакодинамика)
Justification. On average, about 12 % of all global healthcare spending on diabetes. One of the first domestic human insulin preparations was Rinsulin® R, the biosimilar (bioanalog) of Humulin® Regular. The clinical research program for biosimilars of insulin preparations includes pharmacology studies: pharmacokinetics, pharmacodynamics and clinical safety research. Purpose. Evaluation of the biosimilarity of the Rinsulin® R (biosimilar) and Humulin® Regular (original) preparations in the conditions of hyperinsulinemic euglycemic clamp in healthy volunteers. Materials and methods. The study was conducted on healthy male volunteers aged 18 to 50 years. Study design is a double-blind, randomized, cross-sectional study of comparative pharmacokinetics and pharmacodynamics of drugs. The drugs were injected subcutaneously into the anterior abdominal wall at a dose of 0.3 IU / kg once. The duration of blood sampling to determine the pharmacokinetic parameters was 10 hours: the concentration of insulin in the blood was determined by enzyme-linked immunosorbent assay. Based on the level of glycemia, the glucose infusion rate was adjusted, the data of which were used to calculate the pharmacodynamic parameters. Results and discussion. It was found that the studied drugs are characterized by a high degree of similarity of pharmacokinetics and pharmacodynamics. 90 % confidence intervals for the ratios of the geometric mean values of the primary pharmacokinetics AUCins.0-t and Cins.max fully correspond to the permissible limits of 80-125 % and are, respectively, 88.61-111.52 and 85.411-109,51 %. 95 % confidence intervals for the ratios of the geometric mean values of the primary pharmacodynamics AUCGIR0-t and GIRmax fully correspond to the permissible limits of 80-125 % and are, respectively, 93.48-112.29 and 95.75-109.17 %. Of particular clinical significance are the synchronous onset of action of drugs, the time of onset of the maximum effect and duration of action. The frequency of adverse events was comparable in the drug groups. Conclusions. Rinsulin® R and Humulin® Regular are equivalent.